228 LONG TERM OUTCOMES FOR FALLS PATIENTS WHO WERE TREATED BY THE EDITH (EMERGENCY DEPARTMENT IN THE HOME) SERVICE. (25th October 2022) - Davis, AJ; Kenny, L; Delaney, A; Doyle, C; Sweeney, A; Nally, SM; Namara, RM
Abstract: Background: The EDITH service provides an alternative to an ED attendance for the older adult. Medical treatment and Occupational Therapy (OT) assessment take place within the patient's home. Patients who experience an explained fall are routinely treated by the EDITH service, these patients receive OT falls prevention and home environment assessment as standard. It is imperative to assess the long-term outcomes for these patients in order to inform future service provision. Methods: A total of 40 patients, who were referred following an explained fall to the EDITH service and remained at home following assessment, were selected for audit. These patients were seen over a 2-month period in 2021. Data were gathered with regards to ED presentations via healthcare records and mortality rates were captured via RIP.ie Results: At 3 months, 4 patients had re-presented to ED with a fall and 3 required admission. At 6 months, 6 patients re-presented to ED with a fall with 5 requiring admission. At 9 months, 4 patients re-presented to ED with a fall and 3 required admission. 100% of patients had an OT home environment assessment and received advice regarding falls prevention. The average age of patient was 84 years. At 1 year, the mortality rate for this patient group was 10%. Conclusion: Patients with explained falls that were treated by the EDITH service appear to have a reasonably low ED re-attendance rate at 3, 6 and 9 months for explained falls. This may be as a result of the tailored falls prevention education/home environment assessment that took place within the patient's home by the OT. However further audit and a larger population group would be required to suggest a definite correlation between same.